2020
DOI: 10.1209/0295-5075/128/54005
|View full text |Cite
|
Sign up to set email alerts
|

Strange nonchaos in self-excited singing flames

Abstract: We report the first experimental evidence of strange nonchaotic attractor (SNA) in the natural dynamics of a self-excited laboratory-scale system. In the previous experimental studies, the birth of SNA was observed in quasiperiodically forced systems; however, such an evidence of SNA in an autonomous laboratory system is yet to be reported. We discover the presence of SNA in between the attractors of quasiperiodicity and chaos through a fractalization route in a laboratory thermoacoustic system. The observed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Figure 3 shows this bifurcation diagram. Recently, the presence of strange non-chaotic oscillations was reported in the same system [31].…”
Section: Transitions In Laminar Systemsmentioning
confidence: 88%
“…Figure 3 shows this bifurcation diagram. Recently, the presence of strange non-chaotic oscillations was reported in the same system [31].…”
Section: Transitions In Laminar Systemsmentioning
confidence: 88%
“…Grebogi et al [34], for the first time, identified SNA in a quasiperiodically driven dynamical system. The first experimental evidence of SNA in a self-excited system was reported by Premraj et al [72] in the self-excited dynamics of a laminar thermoacoustic system. Strange nonchaotic oscillations are mostly observed between the states of quasiperiodic and chaotic oscillations.…”
Section: Difference Between Strange Chaotic Strange Nonchaotic and Chaotic Nonstrange Signalsmentioning
confidence: 92%
“…4), we witness rich dynamical behavior resulting from a secondary Hopf bifurcation of limit cycle oscillations (see Fig. 9) due to the variation of different control parameters [73][74][75]109,111,178,179,[182][183][184] . In this section, we will discuss the characteristics of these dynamical states and then elaborate different routes to chaos observed in Rijke tube systems.…”
Section: Rich Nonlinear Behavior Of Thermoacoustic Systemsmentioning
confidence: 92%
“…These states include period-2, period-3, periodk, frequency-locked, quasiperiodic, strange nonchaotic, intermittent, and chaotic oscillations. There are many experimental as well as theoretical studies in the thermoacoustic literature that report the existence of these dynamical behaviors in Rijke tube systems 74,75,109,110,150,[177][178][179][180] . Sometimes, a secondary Hopf bifurcation observed due to a change in the control parameter leads to the transition from low amplitude limit cycle oscillations to high amplitude limit cycle oscillations, where both the limit cycle oscillations exhibit the same frequency 28 .…”
Section: Secondary Hopf Bifurcations In Thermoacoustic Systemsmentioning
confidence: 99%

Rijke tube: A nonlinear oscillator

Manoj,
Pawar,
Kurths
et al. 2022
Preprint
Self Cite